2022
DOI: 10.1186/s13018-022-03437-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from miR-338-3p-modified adipose stem cells inhibited inflammation injury of chondrocytes via targeting RUNX2 in osteoarthritis

Abstract: Background Osteoarthritis (OA) is a chronic degenerative disease that is one of the main causes of disability in middle-aged and elderly people. Adipose stem cell (ASC)-derived exosomes (ASC-Exo) could repair cartilage damage and treat OA. MiRNA-338-3p expression was confirmed to play a role in inhibiting proinflammatory cytokines. Herein, we aimed to explore the mechanism by which exosomes derived from miR-338-3p overexpressing ASCs protects chondrocytes from interleukin (IL)-1β-induced chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Furthermore, BMMSC-Exos, delivering the lncRNA LYRM4-AS1, modulated the viability of IL-1β-induced chondrocytes via the LYRM4-AS1/GRPR/miR-6515-5p axis ( Wang et al, 2021 ). Another study confirmed that human umbilical cord-derived MSCs exosomes (UCMSC-Exos) could effectively promote chondrocytes proliferation and migration ( Li et al, 2022 ). It was reported that MSC-Exos derived from embryonic stem cell (ESCMSC-Exos) promoted the proliferation and migration of chondrocytes without affecting matrix synthesis through adenosine-mediated activation of AKT and ERK signaling pathways ( Zhang et al, 2018 ).…”
Section: The Potential Mechanisms Of Msc-exos For Oa Treatmentmentioning
confidence: 89%
“…Furthermore, BMMSC-Exos, delivering the lncRNA LYRM4-AS1, modulated the viability of IL-1β-induced chondrocytes via the LYRM4-AS1/GRPR/miR-6515-5p axis ( Wang et al, 2021 ). Another study confirmed that human umbilical cord-derived MSCs exosomes (UCMSC-Exos) could effectively promote chondrocytes proliferation and migration ( Li et al, 2022 ). It was reported that MSC-Exos derived from embryonic stem cell (ESCMSC-Exos) promoted the proliferation and migration of chondrocytes without affecting matrix synthesis through adenosine-mediated activation of AKT and ERK signaling pathways ( Zhang et al, 2018 ).…”
Section: The Potential Mechanisms Of Msc-exos For Oa Treatmentmentioning
confidence: 89%
“…The encapsulated miR-338-3p within these exosomes is delivered to interleukin-1β-induced ADTC5 cells, promoting the degradation of RUNX2 mRNA. Consequently, this results in the inhibition of cell degradation and apoptosis, alongside the promotion of cell proliferation ( Li et al, 2022 ).Wu Jiangyi et al demonstrated that exosomes secreted by infrapatellar fat pad MSCs can maintain cartilage homeostasis by enhancing autophagy levels, attributed to the inhibition of mTOR. The encapsulated miR-100-5p within these exosomes can bind to the 3′-untranslated region (3′UTR) of mTOR, promoting its degradation.…”
Section: Molecular and Cellular Mechanisms Of Mscs-exosomes In The Tr...mentioning
confidence: 99%
“…In response to treatment with the aforementioned agents, miR155, miR150, and miR 146a remained elevated for at least five days. This suggests that miRNAs are mediators of short-term memory in immune cells as well as MSCs [ 102 ].…”
Section: The Role Of Mirnas In the Modulation Of Immune Responsementioning
confidence: 99%